Strengthening academic bonds: A visit from Fakultas Farmasi, Universitas Halu Oleo, Indonesia / Dr. Mohd Shahezwan Abd Wahab and Associate Prof. Dr. Mahmathi Karuppannan - Abd Wahab, Mohd Shahezwan; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On September 21, 2023, the Faculty of Pharmacy at UiTM hosted a delegation from Fakultas Farmasi Universitas Halu Oleo, Indonesia, signifying a significant milestone in fostering academic collaboration between the two institutions. The delegation included Professor Dr Ruslin, the Dean, and Dr Adryan Fristiohady, the Associate Dean for Student Affairs and Alumni Relations. The visit commenced with a presentation by Dr Mohd Shahezwan Abd Wahab, the Deputy Dean of Academic Affairs at the Faculty of Pharmacy, UiTM, providing an overview of the faculty's background, research achievements, academic programs, and activities. This presentation served as an opportunity for both institutions to exchange valuable insights, explore areas of common interest, and identify potential avenues for collaboration. Subsequently, a lively discussion took place between the Faculty of Pharmacy, UiTM, and the delegates from Fakultas Farmasi Universitas Halu Oleo, led by Professor Dato' Dr Abu Bakar Abdul Majeed, the Dean of the Faculty of Pharmacy, UiTM. The discussions centered around potential collaborative projects, particularly in research and teaching and learning activities.